2021
DOI: 10.1371/journal.pone.0254423
|View full text |Cite
|
Sign up to set email alerts
|

Research on corn production efficiency and influencing factors of typical farms: Based on data from 12 corn-producing countries from 2012 to 2019

Abstract: Globally, corn is characterised by high production and high export concentrations, yet the world is experiencing an unprecedented, huge change in this regard. Ensuring the global supply of corn, and thereby the energy and food security of nations has become particularly important. To understand the importance of corn production as an influencing mechanism of global food supplies, the present study researched the corn production of typical farms in major corn-producing and importing countries around the world. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…1). Argentina, Brazil, USA and Ukraine are the main maize exporting countries of the world, 43 and it is essential for them to have knowledge of the fungi and toxins commonly found in maize stored in silo bags. The average total fungal content in maize grains stored in silo‐bags was 3.13 ± 0.53 × 10 10 cfu kg −1 maize.…”
Section: Fungal Diversity Reported In Maize Stored In Silo‐bags Under...mentioning
confidence: 99%
“…1). Argentina, Brazil, USA and Ukraine are the main maize exporting countries of the world, 43 and it is essential for them to have knowledge of the fungi and toxins commonly found in maize stored in silo bags. The average total fungal content in maize grains stored in silo‐bags was 3.13 ± 0.53 × 10 10 cfu kg −1 maize.…”
Section: Fungal Diversity Reported In Maize Stored In Silo‐bags Under...mentioning
confidence: 99%
“…This part presents various technical efficient levels across countries on different crops and then TE in Tanzania is presented as well. According to a study conducted by Wang & Hu, (2021) in 12 countries (Argentina, Brazil, and Uruguay (South America), Russia, France, Ukraine, Bulgaria, Poland, Czech Republic, and Hungary (Europe), as well as the US (North America) and South Africa) on corn production, the average technical efficiency revealed was 86.3% which imply that these countries are efficient in producing corn and have room to increase their crop outputs by 13.7% with the same inputs. A cross-sectional study conducted in Kenya focusing on Tomato production efficiency by Mwangi et al, (2020), revealed that Kenya is inefficient in producing tomatoes whereby the technical efficiency (TE) level stood at 39.55%.…”
Section: Level Of Technical Efficiencymentioning
confidence: 99%
“…Corn is one of the most widely-planted crops in the world. It is grown in more than 170 regions globally [1]. This sector provides food for most of its population, provides employment for almost all of the existing workforce, produces raw materials, raw materials or aids for the industry and becomes the largest source of foreign exchange earnings [2].…”
Section: Introductionmentioning
confidence: 99%